Laurence-Moon-Bardet-Biedl syndrome- A Case report with review of literature - Marathe, Neha K; Bhat, Pravin M (Indian Journal of Case Reports, 2025)
Laurence-Moon-Bardet-Biedl syndrome (LMBBS) is a rare autosomal recessive (AR) disorder. It has many clinical features out of which ocular manifestations will be discussed in this article along with its ayurvedic correlation. Acharya Sushruta have mentioned Adhyatmika Vyadhis in Sutrasthana which are Aadibala Pravrutta (heridiatory) Janmabala Pravrutta (congenital) and Doshabala Pravrutta. Acharya also elaborates clinical features of Dauhrudavimaanan (not fulfilling desires of pregnant women) in her antenatal phase in Sharirsthana which has resemblance to clinical features of Laurence-Moon-Bardet-Biedl syndrome. This article furthermore mentions a case report of male patient aged 20 years who visited Ophthalmic OPD of Shalakyatantra department in Sane guruji hospital with complaints of diminished vision since childhood, diminished night vision, inability to open right eye completely, lagging of right upper eyelid, delayed developmental milestones.